2018
DOI: 10.3389/fpsyt.2018.00317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3D Contemplative Landscape Videos on Brain Activity in a Passive Exposure EEG Experiment

Abstract: Background: Studies on Contemplative Landscapes (CL) show that not only do they have high ecological and visual values and are preferred by a majority of people, but they also can be beneficial to our mental health and well-being. Physical attributes of CL have been studied and operationalized, which has led to the development of the psychometric measurement tool called the Contemplative Landscape Questionnaire (CLQ) (1).Objectives: In the present study, we applied an experimental approach to the analysis of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 19 publications
2
25
1
Order By: Relevance
“…EEG studies show that the attention shift mechanism is associated with increased temporal beta in the right compared to the left hemisphere [ 28 , 52 ]. A similar pattern appeared in Olszewska’s [ 37 ] study, in which it was found that when participants were observing 3D videos of landscapes classified as the most contemplative, their right temporal brain was more engaged as compared to when they were observing noncontemplative images. In the current study, this pattern occurred with significance only for the ground floor photos with maximal levels of green cover.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…EEG studies show that the attention shift mechanism is associated with increased temporal beta in the right compared to the left hemisphere [ 28 , 52 ]. A similar pattern appeared in Olszewska’s [ 37 ] study, in which it was found that when participants were observing 3D videos of landscapes classified as the most contemplative, their right temporal brain was more engaged as compared to when they were observing noncontemplative images. In the current study, this pattern occurred with significance only for the ground floor photos with maximal levels of green cover.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study by the first author used the EEG method to test the possibility that exposure to certain physical attributes of urban parks and gardens can enhance well-being [ 37 ]. Participants’ brains responded differently to two blocks of stimuli identified as contemplative and noncontemplative landscape settings, presented through still-frame videos in a laboratory setting.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, other studies [72,73] confirm that general mental health improvements may also be attributed to the restoration gained by passive exposure to greenness, independent of exposure gained by actively accessing it for physical activity, and also independent of the mental benefits of the social interaction that can take place in it.…”
Section: Urban Green Blue Infrastructure For Healthy Ageing and Mentamentioning
confidence: 85%
“…Positively rated TV scenes were associated with greater relative left-hemispheric alpha frontal activation, while negatively rated scenes were associated with greater relative right-hemispheric frontal activation. Interestingly, previous within-subjects study on the brain response to contemplative landscape videos, conducted indoors, did not find FAA differences between contemplative and non-contemplative landscape exposure [44]. As for the previous experiments conducted outdoors, they did not examine the FAA patterns, but demonstrated that green urban spaces (often described as nature) triggered improved mood, emotional regulation, recovery from stress and mental fatigue as compared to exposure to space often defined as urban [45][46][47].…”
Section: Discussionmentioning
confidence: 81%